Teknologi Tempa Logam pada Masa Lalu di Daerah Aliran Sungai Pawan, Kalimantan Barat (sebuah pendekatan etnoarkeologi) - Yogi, Ida Bagus Putu Prajna (Balai Arkeologi Maluku, 2016)
Archaeological evidence of metal artifacts found in the area Pawan Watershed in the number of inviting attention to be investigated, that is how the process of technology in the past. The existence of the craftsmen of wrought metal along the watershed area Pawan certainly was not a coincidence. There might be a relationship between the presence of artifacts with traditional metal forging which is still survive until recently. Ethnoarchaeological approach that has been undertaken is expected to give an idea to reconstructs the metal forging technology in the past on Pawan Watershed; to understand the cultural continuity that still exists today in the area. Metal forging technology using the